Petronymphe rara a new species of Oaxaca, Mexico and the rediscovery of P. decora (Asparagaceae: Brodiaeoideae) - Gutiérrez, Jorge; Terrazas, Teresa; Solano, Eloy (Phytotaxa, 2016)
Petronymphe rara is described and illustrated as a new species, endemic to the state of Oaxaca, Mexico, which develops in gypsum soils in the tropical deciduous forest of the Oaxacan Mixteca Alta. This species differs from P. decora, the latter distributed in the state of Guerrero, Mexico, in leaf shape, floral tube size and color and stamen size. We also report the rediscovery of P. decora, a species not collected since 1949 and described in 1951 by Harold E. Moore, including a complete morphological description. In addition, we present an expanded genus description to accommodate the new species.